Aplikasi Audit Manajemen Sumber Daya Manusia Pada PT. Indomitra Prima Lestari Makassar - Nurhadi Nurhadi (Al-Buhuts, 2017)
The aim of this research is to analysis the job unity, which handling human resource in order being successful effectively and efficiently; so the staffs being able to upgrade the company performance. This is a kind of quantitative research, by getting sum or collecting data quantification. The method analysis used is a descriptive analysis, in observing the polices taken by the company in human resources management. The result of this research showsthat selection functions, placementand unwell running of development function. The recommendation of this research needs upgrading the company performance effectively and efficiently, by creating the reliable capacity of human resource at all job division in the unity of company organization.